Motorcycle Tracking System Using Telegram Integrated Quectel L80 GPS - Pri Hartini; Ibrahim Ibrahim; Reni Rahmadewi; Tiara Nurhuda (Universitas Insan Cendekia Mandiri, 2023)
Motorcycles are two-wheeled vehicles that are very common and widely used in Indonesia. At the same time, the criminal rate of motorcycle thieving also has the possibility to increase. The standard security system that motorcycles have is still ineffective. One solution to secure motorcycle from theft is adding a security system. The security system used in this research is a tracking system using a Quectel L80-R GPS connected to an ESP8266 NodeMCU which then installed on a motorcycle. The GPS then integrates with the Telegram application. Users can request the location of the motorcycle by pressing the button on the Chatbot that was previously created. Then the GPS will send a link containing the coordinates of the motorcycle location which can be opened via Google Maps. In this research, the location obtained from the GPS response is quite accurate with an average error distance of 3,06 meters in outdoor tests and 3,51 meters in indoor tests with each 30 trials in 3 different places. Thus, the tracking system using Quectel L80-R GPS can be used properly as a motorcycle security system and has been integrated with the Telegram application.